Legal Reconstruction of the Position of Tax Courts Following the Issue of Constitutional Court Decisions No. 26/PUU-XXI/2023 - Wenceslaus Wenceslaus; Agus Surono; Adnan Hamid; Sonyendah Retnaningsih; Tanawat Teepapal (CV. Era Digital Nusantara, 2025)
As stated in Article 1(8) of the Judicial Power Act, tax courts are special courts under the Supreme Court and part of the judicial branch. According to Article 1(5) of the Tax Court Law, tax disputes are those arising in the field of taxation between taxpayers and authorized officials as a result of a decision that can be appealed or challenged in the Tax Court, in accordance with tax laws and regulations. This includes lawsuits regarding the enforcement of tax collection based on the Tax Collection Act with a Summons. Law No. 17 of 1997 on Tax Collection by Means of a Forced Execution Letter regulates tax disputes arising from tax collection actions by officials that do not comply with legal procedures, causing taxpayers to feel aggrieved. Constitutional Court Decision No. 26/PUU-XXI/2023 is based on Article 24(1) of the 1945 Constitution of the Republic of Indonesia, which states that the Supreme Court and the courts under its authority exercise judicial power. The decision reaffirms that the Tax Court is part of the judicial power and that the Supreme Court must supervise it. Constitutional Court Decision No. 26/PUU-XXI/2023 aims to enhance the Tax Court's independence. Transferring the authority for the organization, administration, and finance of the Tax Court from the Ministry of Finance to the Supreme Court is expected to achieve this goal. Prior to the decision, the Tax Court was under the Supreme Court within the Administrative Court System. The Tax Court was also under the Ministry of Finance in terms of organizational, administrative, and financial supervision in accordance with Article 5(2) of Law No. 14 of 2002 on the Tax Court. However, the arrangement of the status of tax courts following the issuance of Constitutional Court Decision No. 26/PUU-XXI/2023 has raised the issue that the decision does not automatically amend the provisions of Law No. 14 of 2002 on Tax Courts, particularly Article 5(2). According to Constitutional Court Decision No. 26/PUU-XXI/2023, the Supreme Court is responsible for supervising the organization, administration, and finances of the Tax Courts. However, Article 5(2) of Law No. 14 of 2002 of the Republic of Indonesia on Tax Courts grants the Ministry of Finance the authority to supervise the organization, administration, and finances of the Tax Courts. These conflicting provisions result in the loss of the Tax Court's status as an independent judicial institution.